ANALYSIS OF STUDENT DISCIPLINARY BEHAVIOR RELATED TO SCHOOL REGULATIONS - Lusinta Rehna Ginting; Caroline Caroline; Corinne Jessica; Natacia Christela Swandy; Rina Mirza (Faculty of Psychology Universitas Islam Sultan Agung Semarang, 2025)
This study aims to analyze student disciplinary behavior in relation to the implementation of school regulations at SMA Harapan 3 Medan. Discipline is one of the crucial factors that influences learning methods and character development among students within the school environment. The method used in this study is a qualitative approach, with data collection techniques including observation, interviews, and documentation. The research subjects were high school students selected purposively. The results of the study show that the level of student discipline varies and is influenced by personal motivation, teacher support, and school supervision. Discipline impacts the learning environment both positively and negatively. This study identifies the need to enhance supervision over rule violations and strengthen support from teachers and parents in fostering students’ disciplined habits.